Pengaruh Moril Kerja dan Kesediaan Menghadapi Perubahan Terhadap Keterlibatan Kerja Personil Satlantas Di Kepolisian Resort Kota Besar Medan - Abdul Hamid Dalimunte; Saiful Ahyar Lubis; M. Rajab Lubis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study is to see: the influence of work moril and willingness  readiness of changes to the work involvement of satlantas personnel in the Police Resort Kota Besar Medan. The hypothesis proposed is there is a moral influence of work and willingness readiness of changes to work engagement. The research was conducted on 70 Satlantas personnel with sampling techniques is purposive sampling. Data retrieval by scale method is the scale of work engagement, the moral scale of work and the scale of willingness to readiness change. The results showed; 1). There is a significant influence between the morale of work and willingness readiness of changes to work engagement. Coefficient Freg = 110.037; p = 0.000 where p < 0.050. Thus the hypothesis presented in this study is accepted, 2). There was a very significant influence between work morale on work engagement, with a correlation coefficient of 0.716 and an effective contribution of 51.2%. 3). There was a very significant influence between willingness readiness of change and work engagement, with a correlation coefficient of 0.818 and an effective contribution of 66.9%. The moral influence of work and willingness readiness of changes to work engagement is as large. 76,7%. thus there were still 23.3% influenced by other factors not studied in this study.